"People's Diplomacy" - An Important Factor for the Development of Regional Cooperation - Kholmatov Bahodir Kholmuradovich (Peerian Journals Publishing, 2022)
The article discusses the role and importance of «people's diplomacy» in the development of good-neighborly relations and mutually beneficial cooperation between the Central Asian states, and its differences from state diplomacy. He also spoke about the content and essence of the initiatives to make Central Asia a more stable, economically developed, and highly developed region. At the same time, the ongoing geopolitical processes around the region, the concept of «regional cooperation» and the content and essence of the initiatives put forward at the Summit of Central Asian leaders to strengthen security and stability in the region were revealed.
Keywords: Central Asia; the region; diplomacy; people's diplomacy